2004
DOI: 10.1063/1.1786355
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of silicone fluid as a pressure transmitting medium in diamond anvil cells

Abstract: The properties of a silicone fluid with initial viscosity of 1 cst as a pressure transmitting medium for diamond anvil cells have been determined by ruby R1 line broadening and R1-R2 separation measurements to 64 GPa at ambient temperature. By these criteria, the silicone fluid is as good a pressure medium as a 4:1 methanol:ethanol mixture at low pressures to about 20 GPa, and is better than the mixture at higher pressures. Although argon media are better than the silicone at pressures to 30 GPa, this silicone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(63 citation statements)
references
References 31 publications
2
61
0
Order By: Relevance
“…To recover the edge energy of the initial point at 15 GPa, the pressure has to be released down to about 5 GPa. Even if some deviatoric stress effects might exist and lead to some strain in the small poly crystalline grains 26,27 , these effects should be smaller than the observed bond length hysteresis (≈ 0.05Å or 2.5%) in the 10 to 15 GPa range. Zhao and coworkers 32 found in a similar compound a highest strain difference of 0.3% at 6 GPa originating from silicone oil at non-hydrostatic conditions.…”
mentioning
confidence: 83%
“…To recover the edge energy of the initial point at 15 GPa, the pressure has to be released down to about 5 GPa. Even if some deviatoric stress effects might exist and lead to some strain in the small poly crystalline grains 26,27 , these effects should be smaller than the observed bond length hysteresis (≈ 0.05Å or 2.5%) in the 10 to 15 GPa range. Zhao and coworkers 32 found in a similar compound a highest strain difference of 0.3% at 6 GPa originating from silicone oil at non-hydrostatic conditions.…”
mentioning
confidence: 83%
“…In the membrane DAC, samples were loaded in 150-µm-holes drilled in Inconel gaskets and in the Boehler-Almax DAC in 100-µm-holes drilled in tungsten gaskets. Silicone oil was used as pressure-transmitting medium [12,13] and the pressure was measured by means of the ruby fluorescence technique [14]. A pinhole placed before the sample position was used as a clean-up aperture for filtering out the tail of the focused x-ray beam.…”
Section: Methodsmentioning
confidence: 99%
“…[17] Previous studies have shown that pressure gradients result in broadening of the R 1 ruby line [Chai and Brown, 1996;Shen et al, 2004]. An increase in the R 1 À R 2 separation is indicative of the development of deviatoric stress because the wavelength of R 2 is only sensitive to the local mean stress while R 1 is affected by deviatoric stress in the sample [Chai and Brown, 1996;Shen et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the R 1 À R 2 separation is indicative of the development of deviatoric stress because the wavelength of R 2 is only sensitive to the local mean stress while R 1 is affected by deviatoric stress in the sample [Chai and Brown, 1996;Shen et al, 2004]. Therefore, the steep increase in the FWHM of the R 1 ruby line and the R 1 À R 2 separation to about 9 GPa without a pressure medium indicate increases in both the pressure gradients and the deviatoric stress with P. The flattening, or even decrease in the values, occur over the P range reported for the amorphization of non-hydrostatically loaded Ca(OH) 2 [Meade and Jeanloz, 1990;Nagai et al, 2000].…”
Section: Discussionmentioning
confidence: 99%